Mekanisme Perubahan Anggaran Pendapatan Dan Belanja Desa 2020 (Studi Desa Plampaan Camplong Sampang) - Titin Nurhasanah; Agus Sugiono (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to find out how the mechanism or stages of APBDes changes in Plampaan Camplong Sampang Village in 2020. This type of research is qualitative in nature with data collection using observation, interviews and documentation studies.The results of the study concluded that the mechanism or stages of changes to the 2020 Village Revenue and Expenditure Budget in the village of Plampaan Camplong Sampang had the following stages 1) Determine the reason why make the change. 2) The APBDes and RKPDes documents must be in accordance with their activities. 3) Conduct village meetings on changes to the RKPDesa and APBDes with the BPD. 4) The village secretary prepares the APBDes changes that are known by the village head. 5) Evaluating the Draft Village Regulation by the sub-district head regarding the changes to the APBDes. 6) Hold a village meeting in the context of establishing village head regulations regarding the elaboration of APBDes as well as establishing village head regulations regarding changes to APBDes with BPD based on Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management and Regent Regulation No. 06 of 2018 concerning Village Financial Management.